The Influence of Sales and Inventory Turnover on Net Profit in Food and Beverage Subsector Companies Listed on the Indonesia Stock Exchange in 2019-2022 - Alinda; Tri Endar Susianto (Formosa Journal of Social Sciences (FJSS), 2024)
This research was conducted on food and beverage subsector companies listed on the Indonesia Stock Exchange in 2019-2022. The aim of this research is to determine the effect of sales and inventory turnover on net profit in food and beverage subsector companies listed on the Indonesia Stock Exchange in 2019-2022. The research method used is a quantitative method with associative descriptive methods, with data collection techniques using documentation techniques. The population in this study was 40 food and beverage subsector companies and the research sample was 8 companies with 32 secondary data obtained from sampling techniques using Purposive Sampling. The data used is annual financial report data for 4 years from 2019-2022. The data analysis used is panel data regression analysis with Fixed Effect Model estimation which was tested using Eviews 9. Based on the research results, it shows that sales have an effect on net profit with a calculated t value of 15.72687 > t table, namely 2.042272 and a probability value of 0.0000 < 0.05. Inventory turnover has no effect on net profit with a calculated t value of 0.417240 < t table 2.042272 and a probability value of 0.6805 > 0.05. Sales and inventory turnover simultaneously influence net profit with a calculated F value of 972.0746 > F table, namely 3.327654. The coefficient of determination is 0.9974 or 99.74% and the remaining 0.03% is influenced by other variables not examined by researchers